A human-centered design framework for the development of product-service systems - Wong, Thomson Chi Shing (2017)
The synchronized development of products and services are crucial for the success of Product-Service Systems (PSSs). Nevertheless, research has pointed out that the number of service-specific approaches is scarce, and the tools that are mainly used to develop the services in PSS offerings are usually taken from product and software engineering. With the potential to facilitate the understanding of human needs and the emerging cultural and social trends, Human-Centered Design (HCD) may be a feasible design methodology which could be integrated into the development of PSSs. While international standards for the recommendations of HCD principles exist, the appropriate tools and methods that could be utilized for the development of PSSs are not mentioned. This may result in a parochial view and application of the design process. Therefore, a human-centered framework was proposed for the development of PSSs by complementing existing international standards with select HCD, as well as product and service design methods, to supplement existing PSS design models. The goals of this framework were to serve as a starting point to guide the development of PSSs for improved user acceptance and satisfaction, and to assist existing businesses with product-oriented PSSs to identify areas of service improvement and strengthen the long-term relationship with their customers. The Fitbit, a wearable activity tracker, was chosen as an exploratory case study to investigate the significance of HCD in PSSs. This paper concludes with the discussion of findings, as well as the limitations of this study and recommendations for further research.